BASED DESIGN MOBILE LEARNING COURSE ON ANDROID OPERATING SYSTEM IN INDONESIA STMIK PADANG - Liranti Rahmelina (Jurnal Informatika, 2017)
This research in the wake of the habit among students and lecturers in the uses smartphones, mostly only used to access social networks such as facebook and twitter and have yet to take an important role in education. This study aims to produce a system design mobile learning courses Operating Systems in STMIK Indonesia Padang, preferably in the learning process in the subject of the Operating System, the nature of memorization to books and teaching conventional. These mobile devices have a degree of flexibility and portability that enable high students can access materials, referrals and information related to learning anytime and anywhere. mobile learning android ased Operating System. This material requires a solid understanding and so we need learning support media and can be repeated whenever and wherever students need. The design of supporting mobile learning media is expected to facilitate the needs of students and teachers to learn the material at any time without any limitation of time and place. This study uses SDLC (System Development Life Cycle) is a method that describes the system development life cycle in the design and development of information systems. The programming language used is Java, using Eclipse IDE.